A Tetraantennary Glycan with Bisecting N-Acetylglucosamine and the Sda Antigen is the Predominant N-Glycan on Bovine Pregnancy-Associated Glycoproteins - Klisch,K; Jeanrond,E; Pang,P; Pich,A; Schuler,G; Dantzer,V; Kowalewski,MP; Dell,A (Glycobiology, 2008)
Pregnancy-associated glycoproteins (PAGs) are major secretory proteins of trophoblast cells in ruminants. Binucleate trophoblast giant cells (BNCs) store these proteins in secretory granules and release them into the maternal organism after fusion with maternal uterine epithelial cells. By matrix assisted laser desorption ionisation-mass spectrometry (MALDI-MS) analysis and linkage analysis, we show that by far, the most abundant N-glycan of PAGs in midpregnancy is a tetraantennary core-fucosylated structure with a bisecting N-acetylglucosamine (GlcNAc). All four antennae consist of the Sda-antigen (NeuAcα2-3[GalNAcβ1-4]Galβ1-4GlcNAc-). Immunohistochemistry with the mono- clonal antibody CT1, which recognizes the Sda-antigen, shows that BNC granules contain the Sda-antigen from gestation day (gd) 32 until a few days before parturition. Lectin histochemistry with Maackia amurensis lectin (MAL), which binds to α2-3sialylated lactosamine, shows that BNC granules are MAL-positive prior to gd 32 and also at parturition. The observed tetraantennary glycan is a highly unusual structure, since during the synthesis of N-glycans, the insertion of a bisecting GlcNAc inhibits the activity of the GlcNAc-transferases that leads to tri- and tetraantennary glycans. The study defines the substantial changes of PAG N-glycosylation in the course of pregnancy. This promotes the hypothesis that PAGs may have different carbohydrate-mediated functions at different stages of pregnancy.